The teaching profession: knowledge of subject matter, teaching skills and personality traits - Hotaman, Davut (ELSEVIER SCIENCE BV, 2010)
Profession is the phenomenon of vital activity created by division of labor that social, economical and technological factors require. Teaching profession has originated from the social and economical changes that have arisen in societies and can be described as a professional occupational group of education sector possessing social, cultural, economical, scientific and technological dimensions. Profession of teaching is based upon a specialization on a certain field, teaching skills, didactics and some certain personal characteristics that the profession requires. There is a close relation between the fact that individuals who select teaching profession possess the knowledge of subject matter, teaching skills and suitable personality traits and whether the mission which is attributed to this profession is successfully fulfilled. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Profession; teaching; expertise; teaching skills; personality traits; Education & Educational Research